Answer to Question #117355 in Math for Akshay
Find the Laplace transform of f(t)=e^-t,where f(t+1)=f(t)
1
2020-05-21T16:28:24-0400
If "f(t+T)=f(t)," then
"F(s)=L(f(t))={\\displaystyle\\int_{0}^T e^{-st}f(t)dt\\over 1-e^{-sT}}"
"f(t+1)=f(t),\\ f(t)=e^{-t}"
"F(s)=L(f(t))={\\displaystyle\\int_{0}^1 e^{-st}e^{-t}dt\\over 1-e^{-s(1)}}="
"=-{1\\over (1-e^{-1})(s+1)}\\bigg[e^{-(s+1)t}\\bigg]\\begin{matrix}\n 1\\\\\n 0\n\\end{matrix}="
"={1-e^{-(s+1)}\\over (1-e^{-1})(s+1)}"
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Learn more about our help with Assignments:
Math
Comments
Leave a comment